2011
DOI: 10.1002/jmri.22757
|View full text |Cite
|
Sign up to set email alerts
|

Does vertebral bone marrow fat content correlate with abdominal adipose tissue, lumbar spine bone mineral density, and blood biomarkers in women with type 2 diabetes mellitus?

Abstract: Purpose To compare vertebral bone marrow fat content quantified with proton MR spectroscopy (1H-MRS) with the volume of abdominal adipose tissue, lumbar spine volumetric bone mineral density (vBMD), and blood biomarkers in postmenopausal women with and without type 2 diabetes mellitus (T2DM). Materials and Methods Thirteen postmenopausal women with T2DM and 13 age- and BMI-matched healthy controls were included in this study. All subjects underwent 1H-MRS of L1–L3 to quantify vertebral bone marrow fat conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
191
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(219 citation statements)
references
References 38 publications
19
191
3
6
Order By: Relevance
“…First and foremost is the provocative conclusion that it is the composition, rather than the amount, of marrow fat that is correlated with fracture history and diabetes. This finding corroborates previous studies that found lower unsaturation in osteoporosis and in diabetes, both of which involve elevated fracture risk, (5,12) but contrasts with studies that have shown an inverse relationship between the quantity of marrow fat and BMD or bone mass. (3,9,10,13) Additionally, this finding raises the issue of causality-does marrow fat become less unsaturated before a fracture, or afterward?…”
supporting
confidence: 90%
“…First and foremost is the provocative conclusion that it is the composition, rather than the amount, of marrow fat that is correlated with fracture history and diabetes. This finding corroborates previous studies that found lower unsaturation in osteoporosis and in diabetes, both of which involve elevated fracture risk, (5,12) but contrasts with studies that have shown an inverse relationship between the quantity of marrow fat and BMD or bone mass. (3,9,10,13) Additionally, this finding raises the issue of causality-does marrow fat become less unsaturated before a fracture, or afterward?…”
supporting
confidence: 90%
“…Furthermore, MRS-based vertebral bone marrow fat correlated significantly with visceral adipose tissue and HbA1c values in women with type 2 diabetes mellitus. 27 In the context of osteoporosis, MRS-based vertebral bone marrow fat was inversely associated with BMD. 6,7 Patsch et al demonstrated that MRS-based vertebral bone marrow fat composition may serve as a novel tool for BMDindependent fracture risk assessment (28).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to controls without diabetes, higher mean vertebral bone marrow fat content is significantly correlated with visceral adipose tissue and HbA1C in persons with type 2 diabetes, representing worse metabolic profiles (140). The concept of high-saturated fatassociated adipose inflammation and insulin resistance has been proposed; however, underlying molecular mechanisms remain to be elucidated.…”
Section: Bone Marrow Fat Imagingmentioning
confidence: 99%